2012
DOI: 10.1186/1476-511x-11-61
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs2072183 SNP and serum lipid levels in the Mulao and Han populations

Abstract: BackgroundNiemann-pick C1-like 1 (NPC1L1) is a key protein for intestinal cholesterol transportation. Common single nucleotide polymorphisms (SNPs) in the NPC1L1 gene have been associated with cholesterol absorption and serum lipid levels. The present study was undertaken to explore the possible association of NPC1L1 rs2072183 1735 C > G SNP and several environmental factors with serum lipid levels in the Mulao and Han populations.MethodsGenotyping of the rs2072183 SNP was performed in 688 subjects of Mulao an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 59 publications
3
12
2
Order By: Relevance
“…In both the Mulao and Han Chinese subsets, as well as in our data, the rs2072183 minor G allele was associated with an increase in total cholesterol in males. Although Miao et al (27) did not correct for multiple comparisons, we did fi nd a similar effect in our data for NPC1L1 SNP rs17725246, with the SNP effect on total cholesterol (TC) marginally signifi cant in males ( P = 0.054) and not females ( P = 0.94), and the ␤ coeffi cient indicating an increase in cholesterol levels in males only . Thus, we have identifi ed a potential explanation for the reported lack of this SNP's association with total cholesterol in females: differential absorption or processing of dietary cholesterol based on NPC1L1 genotype in males, which is not detectable in females.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In both the Mulao and Han Chinese subsets, as well as in our data, the rs2072183 minor G allele was associated with an increase in total cholesterol in males. Although Miao et al (27) did not correct for multiple comparisons, we did fi nd a similar effect in our data for NPC1L1 SNP rs17725246, with the SNP effect on total cholesterol (TC) marginally signifi cant in males ( P = 0.054) and not females ( P = 0.94), and the ␤ coeffi cient indicating an increase in cholesterol levels in males only . Thus, we have identifi ed a potential explanation for the reported lack of this SNP's association with total cholesterol in females: differential absorption or processing of dietary cholesterol based on NPC1L1 genotype in males, which is not detectable in females.…”
Section: Discussionsupporting
confidence: 52%
“…The overall the marginal effect of the SNP on total cholesterol by gender and found that NPC1L1 SNP rs17725246 marginally predicted total cholesterol in males only (SNP effect ␤ coeffi cient = 5.2, P = 0.054) and not in females ( ␤ = Ϫ 0.243, P = 0.941) in this cohort. We formally tested for a SNPby-sex interaction effect in the prediction of total cholesterol and found it not signifi cant ( ␤ = Ϫ 5.258, P = 0.24); however, we identifi ed a report of this gender interaction in the literature ( 27 ). Although underpowered, we modeled a SNP-by-dietary cholesterol-by-sex interaction in the pooled analyses and found that the rs17725246-sex-dietary cholesterol interaction term was suggestive given limited power (SNP-by-dietary cholesterol-by-sex interaction beta coeffi cient = Ϫ 25.318, P = 0.096).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, it was not associated with cholesterol levels in subjects from Taiwan [55], similar to results obtained elsewhere [56]. Nevertheless, this variant was associated with higher total cholesterol levels in 127 Japanese subjects with Crohn's disease [57] and was documented to cause different plasma lipid profiles between the Mulao and Han populations in China [58]. Recently, the rs2072183 genotype distribution was found to be significantly different in dyslipidemic vs. healthy Japanese individuals [59].…”
Section: Discussionsupporting
confidence: 52%
“…The rs2072183 polymorphism is the top SNP within the NPC1L1 gene most significantly associated with an increased plasma LDL-C level according to a genomewide analysis of Caucasians. However, this polymorphism appears to be associated with reduced LDL-C levels in East Asians 17) , and other recent studies have demonstrated that the rs2072183 polymorphism is associated with increased cholesterol levels in men only and may interact with dietary cholesterol to determine the cholesterol levels 18,19) . It is also possible that mutations in NPC1L1 or polymorphisms in some other genes influencing cholesterol absorption or other pathways inherited from the mother, who also had a low LDL-C level (1.7 mmol/L), may have contributed to the reduced plasma sitosterol, campesterol and LDL-C levels in the affected sibling relative to the proband.…”
Section: Molecular Geneticsmentioning
confidence: 99%